2022
DOI: 10.3389/fimmu.2022.824425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Late and Recurrent Acute Graft Pyelonephritis on Long-Term Kidney Graft Outcomes

Abstract: BackgroundWhile Urinary tract infections are the most common infections in kidney transplant recipients, the impact of late acute graft pyelonephritis (AGPN) on graft outcomes remains unknown. Our study was performed to more precisely evaluate the long-term impact of AGPN.MethodsWe included 9052 kidney and combined kidney-pancreas recipients who underwent transplantation between 2008 and 2018 from a French multicenter cohort. The relationships between AGPN and patient and graft survival were analyzed with a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recent studies that evaluated the impact of AGPN on eGFR showed negative effects on graft survival and eGFR, but in populations with a limited number of old recipients/donors [recipients and donor age 52.6 [40.15–60.7] and 53 [41–62] in Maanaoui et al ( 6 ), and 51.0 ± 14.1 and 52.1 ± 16.4 in Pacaud et al ( 7 )]. Additionally, neither of them routinely prescribed radiological confirmation for an AGPN diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies that evaluated the impact of AGPN on eGFR showed negative effects on graft survival and eGFR, but in populations with a limited number of old recipients/donors [recipients and donor age 52.6 [40.15–60.7] and 53 [41–62] in Maanaoui et al ( 6 ), and 51.0 ± 14.1 and 52.1 ± 16.4 in Pacaud et al ( 7 )]. Additionally, neither of them routinely prescribed radiological confirmation for an AGPN diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, this pathological process has been considered a relatively "benign" condition (22,23). More recently, an increasing number of papers have highlighted the potential role of AGPN in determining reduced graft function and kidney survival (6,7,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ICU setting, acute graft pyelonephritis is the leading cause of around 20% of sepsis cases, and AKI occurrence is typically linked to the development of septic shock [9]. It is an independent risk factor for estimated glomerular filtration rate (eGFR) decline (−2.29 mL/min/1.73 m 2 [95% CI: −3.23 to −1.35]) and graft loss at 1 year (HR: 1.66 [95% CI: 1.05-2.64], although late (i.e., more than 6 months following transplantation) recurrences did not exert a cumulative detrimental effect on allograft survival or on acute rejection frequency [36][37][38]. Although several risk factors for UTIs are widely reported, including donor-related, recipient-related (female gender, advanced age, pre-transplant anatomic abnormalities, diabetes) and transplant-related factors (overimmunosuppression, prolonged placement of ureteral stent), a growing body of evidence highlighted the relevance of the urinary microbiome in the setting of UTIs recurrence and AKI episodes in KTRs [34].…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%